2016
DOI: 10.1038/srep34878
|View full text |Cite
|
Sign up to set email alerts
|

Instability Analysis and Free Volume Simulations of Shear Band Directions and Arrangements in Notched Metallic Glasses

Abstract: As a commonly used method to enhance the ductility in bulk metallic glasses (BMGs), the introduction of geometric constraints blocks and confines the propagation of the shear bands, reduces the degree of plastic strain on each shear band so that the catastrophic failure is prevented or delayed, and promotes the formation of multiple shear bands. The clustering of multiple shear bands near notches is often interpreted as the reason for improved ductility. Experimental works on the shear band arrangements in not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…The proposed fracture mechanisms agree well the fracture morphologies of notched BMGs, giving more theoretical understandings on the controlling of shear-banding in notched BMGs. Li et al [ 83 ] have also conducted theoretical analysis on the controlling of shear-banding in BMGs using an instability theory. As shown in Figure 4 , the formation of shear bands in notched specimens with mode mixities of 0.5 and 0.75 was successfully predicted by instability analysis, which is highly in line with the FEM results and experimental observations [ 83 ].…”
Section: Tunable Plastic Deformation Behavior Under Tailored Complmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed fracture mechanisms agree well the fracture morphologies of notched BMGs, giving more theoretical understandings on the controlling of shear-banding in notched BMGs. Li et al [ 83 ] have also conducted theoretical analysis on the controlling of shear-banding in BMGs using an instability theory. As shown in Figure 4 , the formation of shear bands in notched specimens with mode mixities of 0.5 and 0.75 was successfully predicted by instability analysis, which is highly in line with the FEM results and experimental observations [ 83 ].…”
Section: Tunable Plastic Deformation Behavior Under Tailored Complmentioning
confidence: 99%
“…Li et al [ 83 ] have also conducted theoretical analysis on the controlling of shear-banding in BMGs using an instability theory. As shown in Figure 4 , the formation of shear bands in notched specimens with mode mixities of 0.5 and 0.75 was successfully predicted by instability analysis, which is highly in line with the FEM results and experimental observations [ 83 ]. Such a theory may be further used to predict the shear-banding behavior of BMGs under complex stress fields in practical engineering applications.…”
Section: Tunable Plastic Deformation Behavior Under Tailored Complmentioning
confidence: 99%
“…According to this material model, shear bands are inclined (with respect to the principal stress axes) at the angles where k and ξ = μ / μ * are parameters ruling the state of deviatoric prestress and the incompressible material anisotropy, respectively ( μ and μ * are shear moduli parallel to, and inclined with 45° to, the principle stress axis). Three commonly observed 5 , 6 configurations of shear bands embedded in the material are analyzed, namely, (a) parallel, (b) aligned and (c) converging geometries, arranged as shown in Fig. 1 .…”
Section: Wave Impinging Different Configurations Of Shear Bandsmentioning
confidence: 99%
“…Interaction between shear bands has been documented so far only for quasi-static deformation processes 2 4 , where it has been shown that different shear band geometries emerge as related to load conditions and material properties of the samples and that parallel 5 , aligned, and converging shear bands 6 are frequently observed. In dynamics, results are restricted to high strain-rate loading, where numerical simulations 7 9 and experiments involving impact on prenotched plates 10 12 have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the specific atomic structure, those “defects” in MGs and the interaction between the defects are different from those of the crystal, and leads to different mechanical behavior910. The plastic deformation of the crystalline alloy mainly depends on the dislocation motion, while the plastic deformation in MGs is considered to have two mechanisms at present: shear transition zone (STZ)11 and free volume12.…”
mentioning
confidence: 99%